Suppression of 5′-Nucleotidase Enzymes Promotes AMP-activated Protein Kinase (AMPK) Phosphorylation and Metabolism in Human and Mouse Skeletal Muscle - Kulkarni, Sameer S. (American Society for Biochemistry and Molecular Biology, 2011)
The 5′-nucleotidase (NT5) family of enzyme dephosphorylates non-cyclic nucleoside monophosphates to produce nucleosides and inorganic phosphates. We hypothesized that gene silencing of NT5 enzymes to increase the intracellular availability of AMP would increase AMP-activated protein kinase (AMPK) activity and metabolism. We determined the role of cytosolic NT5 in metabolic responses linked to the development of insulin resistance in obesity and type 2 diabetes. Using siRNA to silence NT5C2 expression in cultured human myotubes, we observed a 2-fold increase in the AMP/ATP ratio, a 2.4-fold increase in AMPK phosphorylation (Thr(172)), and a 2.8-fold increase in acetyl-CoA carboxylase phosphorylation (Ser(79)) (p < 0.05). siRNA silencing of NT5C2 expression increased palmitate oxidation by 2-fold in the absence and by 8-fold in the presence of 5-aminoimidazole-4-carboxamide 1-β-d-ribofuranoside. This was paralleled by an increase in glucose transport and a decrease in glucose oxidation, incorporation into glycogen, and lactate release from NT5C2-depleted myotubes. Gene silencing of NT5C1A by shRNA injection and electroporation in mouse tibialis anterior muscle reduced protein content (60%; p < 0.05) and increased phosphorylation of AMPK (60%; p < 0.05) and acetyl-CoA carboxylase (50%; p < 0.05) and glucose uptake (20%; p < 0.05). Endogenous expression of NT5C enzymes inhibited basal lipid oxidation and glucose transport in skeletal muscle. Reduction of 5′-nucleotidase expression or activity may promote metabolic flexibility in type 2 diabetes.